(untitled) (Madhyabindu Journal, 2024)
Determinants of stock price of Nepalese commercial banks are examined. Primary goal of the study is to analyze, and evaluate the share price fluctuations of Nepalese commercial banks. A descriptive and causal comparative research design was utilized to achieve the objectives of this research. Secondary data will be gathered from the annual reports of sample seven commercial banks, the NEPSE, and other related companies. The MPS has a positive relationship with EPS, P/E ratio, and BVPS but a negative relationship with DPS. It is found that there is a strong positive association between all independent variables (EPS, DPS, BVPS, and P/E Ratio) and the dependent variable (MPS) Examined are the factors that affect Nepalese commercial banks’ stock prices. The analysis and evaluation of Nepalese commercial banks’ share price fluctuations is the study’s main objective. The MPS has a negative relationship with DPS but a positive relationship with EPS, P/E ratio, and BVPS. The study reveals that during the study period of the Nepalese commercial banks, MPS appears to move the greatest, while price earnings ratio fluctuates the least. The study period’s findings also shown a significant positive correlation between commercial banks’ stock prices and their EPS, DPS, P/E ratios, and BVPS. The EPS, DPS, P/E ratio, and BVPS have a considerable positive correlation with the share price of commercial banks.